Comparative quantitative profiling of rare justicidin B in in vitro cultivated Linum species - Rada Nedelcheva; Yancho Zarev; Iliana Ionkova (Pensoft Publishers, 2024)
This research investigates the production and optimization of justicidin B from L. austriacum and L. alpinum in vitro cultures, aiming for high yields of this pharmacologically significant arylnaphthalene lignan. Various cultivation techniques were employed, including shoot, root, and callus cultures, with different media formulations to induce justicidin B biosynthesis. In vitro shoots, callus, and root cultures of both Linum species were successfully established to enhance justicidin B production. Quantification of the lignan was performed using LC-HRESI-MS analysis, comparing the quantities to those of isolated and identified justicidin B from L. leonii hairy root extract. The results show that the in vitro root cultures of L. alpinum produced 1.3 times more justicidin B than those of L. austriacum (7.24 μg/mg DW and 5.31 μg/mg DW, respectively). Additionally, the shoot cultures of L. alpinum yielded 4.5 times more justicidin B than those of L. austriacum (4.34 μg/mg DW and 0.96 μg/mg DW, respectively).